Solid-liquid separation - Svarovsky, Ladislav (Oxford ; Boston : Butterworth-Heinemann, 2000)
Solid Liquid Separation includes important industrial processes used for recovery and processing of solids or purification of liquids. Most of the process industries in which particulate slurries are handled use some form of solid-liquid separation and yet the subject is not adequately covered in most higher education courses. This book is designed to bring the readers up-to-date on the principles and industrial practices of solid-liquid separation and washing technology. Particular attention is given to hardware and to its evaluation, application and selection. Whilst not exclusively concerned with filtration and sedimentation, these operations will be dealt with in depth. Important variations in the available equipment will be discussed throughout the book with emphasis on basic engineering concepts, equipment selection and evaluation, solids washing, methods of pre-treatment, filter aids and other practical aspects of mechanical separation. This book is intended for engineers and scientists of graduate status who are engaged in design, production for research and development. This book is designed to bring the readers up-to-date on the principles and industrial practices of solid-liquid separation and washing technology. Particular attention is given to hardware and to its evaluation, application and selection. Whilst not exclusively concerned with filtration and sedimentation, these operations are dealt with in depth. Important variations in the available equipment are discussed throughout the book with emphasis on basic engineering concepts, equipment selection and evaluation, solids washing, methods of pre-treatment, filter aids and other practical aspects of mechanical separation. This book is intended for engineers and scientists of graduate status who are engaged in design, production for research and development. Author is the top of his field, and knows well all the latest advances in his subject area. Fourth edition of a title which is respected and admired in the world of Chemical Engineering. Updated and revised to match the developments in the industry.
Introduction to solid-liquid separation / L. Svarovsky -- Characterization of particles suspended in liquids / L. Svarovsky -- Efficiency of separation of particles from fluids / L. Svarovsky -- Coagulation and flocculation: Part I -- M.A. Hughes -- Part II: Orthokinetic flocculation / K.J. Ives -- Gravity clarification and thickening / L. Svarovsky -- Hydrocyclones / L. Svarovsky -- Separation by centrifugal sedimentation / L. Svarovsky -- Filter media, filter rating / Lawrence G. Loff -- Filtration fundamentals / L. Svarovsky -- Cake washing / L. Svatovsky -- Methods for limiting cake growth / L. Svarovsky -- Pressure filtration / L. Svarovsky -- Vaccum filtration / L. Svarovsky -- Centrifugal filtration / L. Svarovsky -- Countercurrent washing of solids / L. Svarovsky -- Separator series and networks / L. Svarovsky -- The selection of solid-liquid separation equipment / H.G.W. Pierson -- Particle-fluid interaction, themodynamics of solid-liquid separation / L. Svarovsky.
Includes bibliographical references and index.
Keywords: Separation (Technology); Electronic books